Ethnobotany of Homegarden in The Island of Gili Iyang, Sumenep Regency - Argus, Moh; Hariyati, Jehan Ramdani; Hakim, Luchman; Batoro, Jati (Journal of Indonesian Tourism and Development Studies, 2022)
This study aimed to assess the ethnobotany of home gardens and lad-use units in Gili Iyang Island, Sumenep Regency.  It is expected for future strategic issues, such as global warming mitigation, biodiversity conservation, and food security. This study used an observational method with informal and semi-structured interviews with an indigenous community in Gili Iyang that has a homegarden or yard and uses the plants within for their daily life. Data were analysed by using the Used Values (UVs) and Index of Cultural Significance (ICS). The results showed that there were 63 types of plants located in two places (in the land unit and the homegarden). The community of Gili Iyang widely used the plant of Zea mays L. as the staple food (UVs=1.0), Borrasus flabellifer L. that produce sap (UVs = 0.9), and Lannea coromandelica (Houtt.) Merr.t) for land fence and animal food (UVs 0.9). In the area of the house yard, several plants are often used by the people of Gili Iyang, including the Mangifera indica L for its fruit (UVs=0.8), Piper betle L. for its medicinal use (UVs=0.7), and Manilkara zapota (L.) P. Royen for its fuitr (UVs=0.7). The three-highest ICs were Cocos Nucifera L, Borrasus flabellifer L., and Zea mays L for 162, 136, and 105, respectively, due to their multipurpose uses. Taniyan Lanjheng house and Pamengkang (homegarden) as local custom need to be conserved to support the sustainable cultural and plant conservation effort in Gili Iyang.